Relationship Between Old-Aged Preferences Regarding Various Types of Physical Activity and Chronic Disease Status: A Cross-Sectional Study in Shanghai, China - Huang, Xiaojing; Zhu, Wenqing; Gao, Xiang; Yu, Dehua; Jin, Hua; Huang, Jiaoling; Yu, Wenya; Lv, Yipeng; Zhou, Liang; Chen, Ning; Yang, Yan; Wang, Zhaoxin; et al. (Frontiers in Public Health, 2022)
Background: A lack of physical activity (PA) is a threat to public health. However, for the elderly, most of their PA abilities are limited. By focusing on the types and intensity of PA that the elderly can bear, this study aimed to reveal whether residents’ preferences regarding types of PA (including activities at housework, transportation, recreational activities) and their intensity were associated with their health status. Methods: Surveillance data on chronic diseases and their risk factors were collected from one district of Shanghai from 2017-2018. A Kish table was used for sampling, and 500 older adults were included, including the diagnosed group (diagnosed by physicians who had chronic diseases, n=119), the abnormal group (not diagnosed but abnormal indicators detected in this investigation, n=287) and the healthy group (n=94). Multiple regressions were used to test the relationship between the various types, duration and intensity of PA the elderly individuals participated in and their health status. Results: The three groups had a larger proportion of older adults participating in housework- and transport-related PA, and the diagnosed group had the largest proportion (63.06% for housework-related PA; 87.39% for transport-related PA) and median minutes (17.14 min in housework-related PA per day; 30.00 min in transport-related PA per day). The diagnosed group had more metabolic equivalents (METs) of moderate-intensity PA than the two other groups (H=33.01, P<0.01), and more people met the WHO recommendation (χ^2=34.71, P<0.01). The diagnosis was associated with performing housework- and transport-related PA and moderate-intensity PA and was also associated with meeting the WHO’s recommendation. Higher education levels were a positive factor for elderly individuals to participate in PA. Conclusions: Transportation and activities at housework are better targets for increasing PA in older adults. Diagnosis was associated with old adults’ increased PA.